2019
DOI: 10.3390/md17030163
|View full text |Cite
|
Sign up to set email alerts
|

Target Identification of the Marine Natural Products Dictyoceratin-A and -C as Selective Growth Inhibitors in Cancer Cells Adapted to Hypoxic Environments

Abstract: Hypoxia-adapted cancer cells in tumors contribute to the pathological progression of cancer. The marine spongean sesquiterpene phenols dictyoceratin-A (1) and -C (2) have been shown to induce hypoxia-selective growth inhibition in cultured cancer cells and exhibit in vivo antitumor effects. These compounds inhibit the accumulation of hypoxia-inducible factor-1α (HIF-1α), which is a drug target in hypoxia-adapted cancer cells, under hypoxic conditions. However, the target molecules of compounds 1 and 2, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…3Currently developed inhibitors of R2TP core components. Compound 1, Liddean, and Dictyoceratin-A/-C interact with RUVBL1, RUVBL2, and RPAP3, respectively [46,47,50]. R2TP/PAQosome promotes cancer development by chaperoning mTORC1 and snoRNP, and it may confer chemotherapy and ionizing radiation resistance to ATM-deficient cancers by activating ATR.…”
Section: Oncogenesis-related Function Of R2tp/paqosomementioning
confidence: 99%
See 1 more Smart Citation
“…3Currently developed inhibitors of R2TP core components. Compound 1, Liddean, and Dictyoceratin-A/-C interact with RUVBL1, RUVBL2, and RPAP3, respectively [46,47,50]. R2TP/PAQosome promotes cancer development by chaperoning mTORC1 and snoRNP, and it may confer chemotherapy and ionizing radiation resistance to ATM-deficient cancers by activating ATR.…”
Section: Oncogenesis-related Function Of R2tp/paqosomementioning
confidence: 99%
“…Subsequently, they found that the dictyoceratin-A and -C showed hypoxia-selective proliferative inhibitory activity against prostate cancer cells, DU145 [49]. Recently, they identified that RPAP3 is the target of dictyoceratin-A and -C [50]. When DU145 cells were grown in hypoxic condition, the protein levels of HIF-1α (Hypoxia-Inducible Factor), which is a key regulator of oxygen homeostasis involved in tumor proliferation in hypoxia, were significantly elevated.…”
Section: R2tp As a Chemotherapeutic Target For Cancermentioning
confidence: 99%
“…Among others, SPINT2 was associated with metastatic osteosarcoma [54], ovarian cancer [55], glioma/glioblastoma [56,57], prostate cancer [58] and non-small lung cancer [59], leukemia [60] and cervical carcinoma [61]. RPAP3, essential for assembling chaperone complexes [62], was linked to hypoxia-adapted cancer cells [63] and BZW,1 was associated with ovarian [64], lung [65] and salivary gland [66] cancers. However, we found no mention in the literature about the role of these first three genes in any form of thyroid cancer.…”
mentioning
confidence: 99%
“…Some of the marine-derived compounds have been reported to inhibit the growth of cancer cells adapted to the hypoxic or nutrient-starved conditions. For example, furospinosulin-1 (furanosesterterpene) and dictyoceratins-A and -C (sesquiterpene phenols) isolated from the marine sponge Dactylospongia elegans were shown to exhibit the selective growth inhibitory activities against the hypoxia-adapted human prostate cancer cell line DU145 [ 4 , 5 ]. Recently, we reported the cytotoxic activities of polybrominated diphenyl ethers, N -methylniphatin A (new 3-alkyl pyridine alkaloid) and biakamides (unique new polyketides) isolated from Indonesian marine sponges of Dysidea sp., Xestospongia sp., and Petrosaspongia sp., respectively, against human pancreatic carcinoma cell line PANC-1 adapted to glucose-deficient growth conditions [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%